Borrowing Strategy for Words Related to Covid-19 Pandemic in Running Texts on Indonesian Tv Channels - Budi Purnomo (Faculty of Language and Literature, University of Surakarta, 2021)
This study attempts to investigate the borrowing strategies used by Indonesian TV channels to translate words related to covid-19 pandemic displayed in the running texts along with their readability and acceptability. The research is a descriptive and qualitative in nature. The data were collected by note-taking, analysis, questionnaire of running texts and test techniques in the form of sentences containing borrowed words from source language (English) into target language (Indonesian). To know the types of borrowing strategies, the borrowed words and the language was analysed based on the writer’s borrowing classification. The parameter of readability was used to assess the readability of the borrowed words and the criteria of acceptability were applied to explain their acceptability. The research findings show that the most widely used strategy for borrowed words in the running texts of Indonesian TV channels is transliteration. In addition, most of the borrowed words they used are less readable and less acceptable